2006
DOI: 10.1007/s00246-005-1022-4
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Concentrations of N-Terminal Brain Natriuretic Peptide in Healthy Children, Adolescents, and Young Adults: Effect of Age and Gender

Abstract: Children with congenital heart disease need adequate diagnostic classification regarding their cardiovascular status (CVS). N-terminal brain natriuretic peptide (N-BNP) plasma concentration indicates dysfunction of the cardiovascular system and guides decisions concerning treatment and prognosis. Reference values are established for adults, with age-dependent increasing values and higher values in women. To avoid misclassification concerning the CVS, a large group of healthy children and adolescents can be use… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(50 citation statements)
references
References 22 publications
3
45
0
1
Order By: Relevance
“…CHF. Plasma BNP concentrations are higher in women than in men (23). In the present study, we showed that the NPPB gene is a key source of inter-individual variation in plasma BNP levels.…”
Section: Association Of Polymorphisms At Nppb With Plasma Bnp Levelssupporting
confidence: 59%
“…CHF. Plasma BNP concentrations are higher in women than in men (23). In the present study, we showed that the NPPB gene is a key source of inter-individual variation in plasma BNP levels.…”
Section: Association Of Polymorphisms At Nppb With Plasma Bnp Levelssupporting
confidence: 59%
“…This is particularly important for the pediatric population, 50 where the high rates of growth and development can alter the other-51 wise predicted levels of many analytes [1][2][3][4][5]. The use of adult reference 52 intervals for the interpretation of pediatric test results, a common prac-53 tice in many healthcare centers worldwide, is inappropriate, and 54 represents a major source of post-analytical error that can lead to 55 patient misdiagnoses and inappropriate treatment decisions [6][7][8][9]. 56 The lack of pediatric-specific reference intervals has remained a 57 major problem in the pediatric setting due to the difficulty in collecting 58 samples from healthy community children, particularly from young 59 children and infants, where only a small blood volume can be obtained.…”
mentioning
confidence: 99%
“…В противоположность этому сре-ди детей старше 10 лет наблюдали достоверное превы-шение концентраций BNP в группе мальчиков по срав-нению с девочками (12,1 и 5,1 пг/мл соответственно). Кроме того, плазменная концентрация BNP у девочек в пубертатном возрасте достоверно выше, чем в препу-бертатном (14,4 и 7,1 пг/мл соответственно) [34], что не противоречит другим работам [31,[35][36][37][38][39]. По данным статьи Nir A.…”
Section: диагностические уровни натрийуретических пептидовunclassified